(3ahGJ GdhajGJs - (3eMeO Hf TGcQ Hf CMeO Hf YHO GdQMef GdcJHj GdOGQGfqj GdOeTbqj, UdGM GdOjf , GHf TGcQ J (B764 (3g` s
(3ChdgG (B:s
(3JQLeI eMeO Hf Ydi Hf YeQ GdeGRfi s
(3BNQgG (B:s
(3JQLeI jhfS Hf eeOhO Hf CjhH GdSdWGf Gdedc GdLhGO s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B1185s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B328 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B201 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs